2017
DOI: 10.1149/2.0511709jes
|View full text |Cite
|
Sign up to set email alerts
|

Inverse Crevice Corrosion of Carbon Steel: Effect of Solution Volume to Surface Area

Abstract: Crevice corrosion of carbon steel was investigated in different exposure environments by performing coupon exposure and electrochemical tests. The extent of corrosion on the bold surface of a carbon steel crevice coupon was more severe at 80 • C than at 21 • C, in aerated rather than dearated solutions, and with γ-radiation present. In contrast to normal crevice corrosion, we observed 'inverse crevice corrosion' behavior, the phenomenon where it is the corrosion on the bold surface that is accelerated when cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…26 Multiple electron transfer steps are more common for metal redox halfreactions because transition metal cations have more than one stable oxidation state in solution. [27][28][29][30][31][32][33] Thus, depending on E corr and mass transport conditions, polarizing E elec away from E corr can change the rate determining step, resulting in a current-potential relationship very different from that at E . corr The perturbation of E elec away from E corr and the uncertainties in the analysis of the observed dependence of i meas on E elec can result in incorrect determination of i ox at E corr (i.e., i corr ), consequently leading to the development of an inaccurate corrosion model.…”
Section: The Individual Concentrations O Intmentioning
confidence: 99%
“…26 Multiple electron transfer steps are more common for metal redox halfreactions because transition metal cations have more than one stable oxidation state in solution. [27][28][29][30][31][32][33] Thus, depending on E corr and mass transport conditions, polarizing E elec away from E corr can change the rate determining step, resulting in a current-potential relationship very different from that at E . corr The perturbation of E elec away from E corr and the uncertainties in the analysis of the observed dependence of i meas on E elec can result in incorrect determination of i ox at E corr (i.e., i corr ), consequently leading to the development of an inaccurate corrosion model.…”
Section: The Individual Concentrations O Intmentioning
confidence: 99%
“…Such environments include water with strongly alkaline pHs and solutions containing certain anions such as carbonates/bicarbonates, chromates and halides. Similar anoxic crevice conditions are also expected to be developed during the long term storage of high-level radioactive waste in the deep repository disposal site boreholes lined with metallic canisters of stainless steel or low alloy carbon steel) embedded in clay [22 24].…”
Section: Resultsmentioning
confidence: 99%
“…Crevice corrosion of carbon and low-alloy steels has been discussed by several researchers. Wu et al [15] observed higher rates of corrosion on a carbon steel surface exposed to a bulk electrolyte compared to a surface within a crevice. The term inverse crevice corrosion was introduced due to more aggressive corrosion being observed on a bare sample after galvanically coupling with a crevice sample.…”
Section: Introductionmentioning
confidence: 99%
“…The term inverse crevice corrosion was introduced due to more aggressive corrosion being observed on a bare sample after galvanically coupling with a crevice sample. Wu et al [15] proposed that carbon steel corrosion in a crevice involves many oxidation steps that lead to metal dissolution and formation of different oxides. Therefore, the solution volume to surface area ratio and solution chemistry have a significant effect on crevice corrosion.…”
Section: Introductionmentioning
confidence: 99%